Strength training for swimmers - Mujika, I.; Crowley, E. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
This chapter covers the impact of strength training for swimming performance (free swimming, starts, and turns); its effects on swimming biomechanics; dry-land and in-water strength training methods; and the periodization of strength training for swimming performance. Abstract from author